Design of a Series Elastic Transmission for hand exoskeletons. (May 2018) - Bianchi, M.; Cempini, M.; Conti, R.; Meli, E.; Ridolfi, A.; Vitiello, N.; Allotta, B.
Abstract: Recently, the wearable robotic field has become extremely prolific in terms of active devices for human body assistance. Nevertheless, unfortunately, owing to strictly motor and sensor requirements in terms of mechanism, weight, size and dexterous manipulation capabilities, portable hand exoskeletons for rehabilitation and assistance have not been developed as much as the exoskeletons for lower and upper limbs; in fact, only a few of them present an outcome of their use in the clinical practice as positive as expected. This research work aims at designing an aid for the hand function based on exoskeleton technologies for patients who have lost or injured their hand skills. In particular, this paper presents a novel Series Elastic Transmission (SET) used as power transmission on a Hand Exoskeleton System (HES) based on a Series Elastic Actuator (SEA). The elastic element of the transmission has been designed through the innovative topology optimization approach which has led to manufacture a component whose mechanical features strictly replicate the desired ones. The authors have validated the proposed approach by testing a real elastic component. Suitable mechanical tests, whose results are reported in the paper, were executed in order to evaluate the goodness of the design procedure.